(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
Social media has become an alternative source of information for Vietnamese people in recent years. Students reading Media and Communication (MC) at University use social media with a high frequency to partly fulfill requirements deriving from their courses’ projects. Meanwhile, students reading in other majors may use social media less than MC students. Differences in needs to fulfill courses’ requirements could be the reason for the high volume of use of social media by MC students. This raises the question of whether information-seeking needs could influence the use of social media networking sites as sources of preferences. However, there is a lack of studies on this phenomenon. To explore this phenomenon, the study employs the social media use, individual variations in social media use for information seeking, and the theory of uses and gratifications. This is expected to demonstrate the difference between students of the same major selecting find out why students like that social network over other social platforms while choosing among Facebook and TikTok as platforms for information gathering. The process of teaching young people to use social media more deliberately will be aided by this study. The academic contribution is the behavior of young people using social networks in Vietnam.